The wonderful world of pyridine-2, 6-dicarboxamide based scaffolds. Issue 47 (7th November 2016) - Kumar, Pramod; Gupta, Rajeev
Abstract : This perspective focusses on a variety of scaffolds based on a pyridine-2, 6-dicarboxamide fragment and their noteworthy roles in coordination chemistry, biomimetic studies, catalysis, and sensing. Abstract : The present perspective focusses on a variety of scaffolds based on a pyridine-2, 6-dicarboxamide fragment and their noteworthy roles in coordination chemistry, stabilization of reactive species, synthetic modelling of some metalloenzyme active sites, catalytic organic transformations, and sensing as well as recognition applications. These examples illustrate the significance of synthetic scaffolds based on the pyridine-2, 6-dicarboxamide fragment in synthetic chemistry in general and coordination chemistry in particular.